Interstitial 13q14 deletions detected in the karyotype and translocations with concomitant deletion at 13q14 in chronic lymphocytic leukemia: Different genetic mechanisms but equivalent poorer clinical outcome. Issue 9 (10th June 2014) - Puiggros, Anna; Venturas, Marta; Salido, Marta; Blanco, Gonzalo; Fernandez‐Rodriguez, Concepción; Collado, Rosa; Valiente, Alberto; Ruiz‐Xivillé, Neus; Carrió, Ana; Ortuño, Francisco José; Luño, Elisa; Calasanz, María José; et al.
<x xml:space="preserve">Abstract</x> Deletion of 13q14 as the sole abnormality is a good prognostic marker in chronic lymphocytic leukemia (CLL). Nonetheless, the prognostic value of reciprocal 13q14 translocations [t(13q)] with related 13q losses has not been fully elucidated. We described clinical and biological characteristics of 25 CLL patients with t(13q), and compared with 62 patients carrying interstitial del(13q) by conventional G‐banding cytogenetics (CGC) [i‐del(13q)] and 295 patients with del(13q) only detected by fluorescence in situ hybridization (FISH) [F‐del(13q)]. Besides from the CLL FISH panel (D13S319, CEP12, ATM, TP53), we studied RB1 deletions in all t(13q) cases and a representative group of i‐del(13q) and F‐del(13q). We analyzed NOTCH1, SF3B1, and MYD88 mutations in t(13q) cases by Sanger sequencing. In all, 25 distinct t(13q) were described. All these cases showed D13S319 deletion while 32% also lost RB1. The median percentage of 13q‐deleted nuclei did not differ from i‐del(13q) patients (73% vs. 64%), but both were significantly higher than F‐del(13q) (52%, P < 0.001). Moreover, t(13q) patients showed an increased incidence of biallelic del(13q) (52% vs. 11.3% and 14.9%, P < 0.001) and higher rates of concomitant 17p deletion (37.5% vs. 8.6% and 7.2%, P < 0.001). RB1 involvement was significantly higher in the i‐del(13q) group (79%, P < 0.001). Two t(13q) patients (11.8%) carried NOTCH1 mutations. Time to first treatment in t(13q) and i‐del(13q) was shorter than F‐del(13q) (67, 44, and 137 months, P = 0.029), and preserved significance in the multivariate analysis. In conclusion, t(13q) and del(13q) patients detected by CGC constitute a subgroup within the 13q‐deleted CLL patients associated with a worse clinical outcome. © 2014 Wiley Periodicals, Inc.